(untitled) (Damascus University Journal of Historical Studies, 2022)
This research deals with the period between (1919-1939) this period when Algeria witnessed the emergence of a new type of resistance, namely political resistance represented by the national movement, which is considered one of the most important liberation movements in Algerian history, due to the efforts it has made in confronting France’s educational policy. This is done through its revival of traditional education, its promotion of free education and its construction of national schools, as well as clubs and associations through which it tried to spread its libertarian ideas, which France was alerted to its danger and pursued its members, exiled them and closed some of its parties. However, this did not dissuade the national movement from continuing its educational project, which confirms its continued construction of educational schools until 1939. The research concluded that the national movement has succeeded in achieving its goals of preserving the Algerian identity and returning Algeria to the Arab home, as evidenced by the increasing numbers of Algerian learners coming to Algerian national schools instead of French schools.